News Structure of KRI Ardadedali-404 at Merdeka.com - Hidayat, Ashari (MUHARRIK: Jurnal Dakwah dan Sosial, 2022)
KRI Ardadedali-404 is a submarine for the Indonesian Navy's defense equipment (alutsista) production cooperation with South Korea. The presence of the new defense equipment has attracted the attention of the news media to cover it. The news media bridge the information needs of defense equipment through news discourse. Merdeka.com as a news media that provides space for reporting on defense equipment, displays the presence of KRI Ardedali-404 in a descriptive discourse structure. This study aims to explore the structure of reporting on KRI Ardadedali-404 as a news object within the framework of the activity of sending information from the media to the public. The linguistic theory that places news as a unit of informational discourse and the product of context-bound linguistic activity is used in this study. The research method uses structural contextual analysis through observation and interview techniques to understand media procedures in the reporting process. Exposure analysis is done by sorting out the sequences of information constructing discourse. The results of the research are 1) the descriptive structure pattern of the news is built through the stages of introduction, identification, and specification; 2) the elements of filling the news section to describe the news object are conveyed into parts of the news structure. The conclusion obtained is that the news of KRI Ardedali-404 is designed in a descriptive discourse structure choice through the fabric of information from simple to complex and the fulfillment of the completeness of news elements through highlighting exploration in the stem of the discourse.